Early intervention and disease memory in psoriasis: A literature review - Hakim Ben Abdallah; Thomas Emmanuel; Anne Bregnhøj; Claus Johansen; Lars Iversen (Wiley, 2022)
Abstract Psoriasis is a chronic inflammatory skin disease, in which molecular and cellular changes retain following clinical resolution of psoriatic lesions, a form of disease memory ('molecular scar') that may reestablish the psoriatic inflammation. The increasing evidence of the benefits from early intervention in other immune‐mediated diseases prompts the question of whether early systemic intervention, such as biologics, in new‐onset cutaneous psoriasis may lead to improved clinical response and sustained remission by averting an inflammatory disease memory. Herein, we review the current evidence on early intervention and disease memory in psoriasis. The evidence is sparse and inconsistent, although an early intervention within 2 years of disease‐onset may provide a more favourable long‐term prognosis in psoriasis. However, ongoing randomised clinical trials will explore whether early intervention with biologics in new‐onset psoriasis will be an effective treatment strategy, and whether it prevents the molecular and cellular changes potentially underlying the inflammatory disease memory.